Successful pregnancy in Didelphys uterus: a case report - Laya Shirinzadeh; Maliheh Rakhshanifar (Mashhad University of Medical Sciences, 2021)
Introduction: Didelphys uterus is one of the rare cases of mullerian anomalies that in most cases, remains asymptomatic until pregnancy and delivery. In women with mullerian anomalies, pregnancy and delivery are associated with more complications such as preterm labor that requires more attention to such pregnancies. Most cases of pregnancies in Didelphys uterus are reported in the left cavity. Ultrasound and MRI can be used to diagnose it. Case presentation: The patient was a 21 year old female with history of dyspareunia and one spontaneous abortion at 38 weeks of pregnancy who referred to the maternity complaining of amniotic fluid leakage and labor pain. Longitudinal vaginal septum was diagnosed during the vaginal examination. The patient underwent a cesarean section due to thick meconium-stained amniotic fluid far from delivery and a healthy term baby was born. Didelphys uterus was seen and the fetus was in the right cavity. Conclusion: Despite the high incidence of pregnancy complications in pregnancies with mullerian anomalies, sometimes these pregnancies continue without complications until term.